PEISAJUL RURAL DIN COMUNA CERGĂU (PANGEEA, 2025)
The countryside of Cergău village. Cergău village is situated in the plateau that bears the same name and is part of the Secaşelor Plateau. A careful study of the local geography of the village reveals that the geographical landscape is not as dull as one might think , bat has a few intresting varieties landscape. In the recent years the landscape has continuously being changing due to the actions of sevrals factors. Some of these factors are of antropogenic origin, others are physical and geographyc factors. Their actions is either independent or mixted and the results are visible everywhere. The hils are gentle slopes and their gradients are various, which are subjected to deforestation and erosive actions or they have beem tailored for agricultural purposes. There is a mixture of cultivated and non- cultivated land, parts of the former forest and vast areas of pastures and meadows amongst which these villages are spread. These villages belong to the category of rural settlements, bat their pozitions in the valley of Cergău river, lead to a concentrations of housing which distinguishes them from the tipically scattered caryathion subcarpathyc villages. Key words: landscape, erosion, hils, slope, deforestation, human activity.